IL-33 Inhibits Hepatitis B Virus through Its Receptor ST2 in Hydrodynamic HBV Mouse Model. (28th April 2020) - Gao, Xiuzhu; Chi, Xiumei; Wang, Xiaomei; Wu, Ruihong; Xu, Hongqin; Zhan, MengRu; Li, Dong; Ding, Yanhua; Xu, Damo; Niu, Junqi
Abstract : Interleukin-33 has been demonstrated to be associated with liver damage. However, its potential value in hepatitis B virus (HBV) infection remains unknown. This study was designed to investigate the role of IL-33 in hydrodynamic HBV mouse model. Different doses of IL-33 were used to treat HBV wild-type, ST2 knockout, CD8+ T depletion, NK depletion C57BL/6 mice and C.B-17 SCID and nod SCID mouse, respectively. The concentrations of HBV DNA, HBsAg, HBeAg, and molecules related to liver function were detected in the collected serum at different time points from model mice. Intrahepatic HBcAg was visualized by immunohistochemical staining of liver tissues. In vitro, hepG2 cells were transfected with pAAV-HBV 1.2, then treated with IL-33. The results showed that IL-33 significantly reduced HBV DNA and HBsAg in a dose-dependent manner in HBV wild-type mice. However, in the IL-33 specific receptor ST2 knockout mice, their antiviral effects could not be exerted. Through immunodeficient animal models and in vivo immune cell depletion mouse model, we found that IL-33 could not play antiviral effects without NK cells. Moreover, IL-33 could reduce the levels of HBsAg and HBeAg in the supernatant of HBV-transfected hepG2 cells in vitro . Our study revealed that IL-33 could inhibit HBV through ST2 receptor in the HBV mouse model, and this effect can be impaired without NK cell. Additionally, IL-33 had the direct anti-HBV effect in vitro, indicating that IL-33 could be a potent inducer of HBV clearance and a promising drug candidate.